Surgical Expertise in Neonatal Extracorporeal Membrane Oxygenation (ECMO): A Single Center Experience - Macchini, Francesco; Di Cesare, Antonio; Morandi, Anna; Ichino, Martina; Raffaeli, Genny; Conigliaro, Federica; Sorrentino, Gabriele; Neri, Simona; Mosca, Fabio; Leva, Ernesto; Cavallaro, Giacomo (Frontiers in Pediatrics, 2019)
Introduction: The surgical technique for peripheral cannulation aimed at providing extracorporeal membrane oxygenation (ECMO) is well described. Training methods for surgeons still need proper standardization, especially in newborn patients. This study aims to evaluate the surgical training outcomes of a neonatal ECMO team. Materials and Methods: A 4 year training program (2014–2018) was developed to achieve the skills in the surgical technique for neonatal veno-arterial ECMO. Surgeons with experience in neonatal and vascular surgery were selected for the training. The training consisted of educational sessions, high-fidelity simulations, in vivo swine model procedures, international fellowship, and periodical simulations. The preliminary clinical experience in surgical neonatal ECMO management (2016-present) was analyzed by recording the following data: indications for ECMO and patients' data; effectiveness of cannulations (number; perioperative complications of cannulation; major surgical events during ECMO); efficacy of decannulation (number and perioperative complications). Results: 12 neonates (5 females) fitted the ELSO criteria for ECMO. Nine newborns were affected by CDH; 1 by H1N1 flu-related pneumonia; 1 by meconium aspiration syndrome and one by Respiratory Syncytial Virus related bronchiolitis. Mean weight at cannulation was 3,281 g (range 2,330–3,840 g); mean gestational age was 36 weeks. No procedure was aborted, and no intra-operatory mortality was recorded. Mean operative time was 86 ± 30 min. The caliber of the carotideal cannulas ranged from 8F (8 patients) to 10F (2 patients); the caliber of the jugular cannulas were: 8F cannula (2 patients), 10F (6 patients), and 12F (2 patients). Four complications occurred: a case of air in the circuit, two cases of azygous vein cannulation and a partial dislocation of the venous cannula during the daily care maneuvers. All of them were promptly recognized and successfully treated. The mean ECMO duration was 7.1 ± 4.2 days (range 2–16 days). Seven patients (78%) were decannulated effectively. Mean decannulation time was 53 min (range 45–80 min). No complications occurred during the decannulation process. No ECMO–related deaths were recorded. Conclusions: Neonatal respiratory ECMO still represents a challenge. Experienced neonatal surgeons can manage the neck vascular cannulation. The codified procedure must be adhered to after appropriate training and following a proper learning curve.